2002
DOI: 10.1006/aphy.2002.6233
|View full text |Cite
|
Sign up to set email alerts
|

Faster-than-c Signals, Special Relativity, and Causality

Abstract: Motivated by the recent attention on superluminal phenomena, we investigate the compatibility between faster-than-c propagation and the fundamental principles of relativity and causality. We first argue that special relativity can easily accommodate-indeed, does not exclude-faster-than-c signaling at the kinematical level. As far as causality is concerned, it is impossible to make statements of general validity, without specifying at least some features of the tachyonic propagation. We thus focus on the Scharn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
189
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(190 citation statements)
references
References 71 publications
1
189
0
Order By: Relevance
“…For the matter model discussed in [12] the superluminality is identified in [13] as originating in renormalization of a negative bare mass and gives rise to kinetic energies with no lower bound (and 6 hence without a well-defined ground state). In [16] the superluminal velocities which are found in the Scharnhorst effect (where they are due to QED corrections in the Casimir effect) are argued not to lead to causality violations because they define a causal cone in the frame of the Casimir plates which can used to redefine causality in the same way as the sound cones discussed above; however, they exist only locally between the plates and therefore cannot be used to signal. It is also possible to construct lattice models with p > ρc 2 and dp/dρ > c 2 , but the sound speed (i.e.…”
Section: Microscopic Fluid Modelsmentioning
confidence: 97%
“…For the matter model discussed in [12] the superluminality is identified in [13] as originating in renormalization of a negative bare mass and gives rise to kinetic energies with no lower bound (and 6 hence without a well-defined ground state). In [16] the superluminal velocities which are found in the Scharnhorst effect (where they are due to QED corrections in the Casimir effect) are argued not to lead to causality violations because they define a causal cone in the frame of the Casimir plates which can used to redefine causality in the same way as the sound cones discussed above; however, they exist only locally between the plates and therefore cannot be used to signal. It is also possible to construct lattice models with p > ρc 2 and dp/dρ > c 2 , but the sound speed (i.e.…”
Section: Microscopic Fluid Modelsmentioning
confidence: 97%
“…Indeed, it is by now well known that it is quite easy and ubiquitous to obtain emergent Lorentz symmetries in Galilean systems, through the presence of Fermi points [25,26]. In [26,31,32] it is shown how the use of Lorentzian notions might be just an epistemological election, appropriate for the description of a system by internal observers that do not want to use fiduciary external extructures in their description. For example in [32] it was shown that one can obtain the phenomenology of special relativity, for example the Michelson-Morley experiment, within an emergent scenario of low-energy fields living in a fiduciary external Galilean world.…”
Section: Jhep10(2016)084mentioning
confidence: 99%
“…As it is well known, the L-L theory has problems of stability and admits propagation of superluminal signals [18]. This last fact, as shown in papers [19] and [20], implies violations of causality. In order to avoid causality violation problems, some theories of viscous fluid, that incorporate second order gradients in the velocities, have been developed [21], [22].…”
Section: Introductionmentioning
confidence: 95%